Safety and Clinical Evaluation of a Sonic Tongue Brush - Satoshi Shirakawa; Takatoshi Nagano; Yuji Matsushima; Akihiro Yashima; Kazuhiro Gomi (Elsevier, 2024)
Background: Tongue coating consists of oral bacteria, desquamated epithelium, blood cells, and food residues and is involved in periodontal disease, halitosis, and aspiration pneumonia. Recently, a tongue brush with sonic vibration was developed to clean the tongue. This comparative study examined the extent of tongue coating, its effects on the tongue, bacterial count particularly on the posterior dorsum of the tongue, and the degree of pain using a manual tongue brush and the newly developed sonic tongue brush. Materials and methods: Patients' extent of tongue coating and the quantity of bacteria were analysed before and after brushing with a sonic or manual nylon tongue brush. Moreover, the impressions of the dorsum linguae were obtained before and after brushing to establish models that were observed under a stereo microscope to evaluate tongue trauma. Pain caused during the use of these brushes was evaluated based on the numerical rating scale (NRS). Results: The extent of tongue coating and number of bacteria decreased in both the sonic and manual nylon brush groups after tongue cleaning; however, no significant differences were noted. Tongue trauma evaluation revealed that the tongue surface was significantly scratched in the manual brush group compared with the sonic brush group. NRS-based pain evaluation revealed no significant differences. Conclusions: The sonic brush was equally effective in removing tongue coating and bacteria compared with the manual brush. As the sonic brush does not cause tongue trauma, it may be considered a safe and effective cleaning tool of the tongue.